How to Apply the Process Skills Approach to Improving Indonesian Language Learning Outcomes in Senior High Schools - Firman Firman; Mirnawati Mirnawati; Usman Usman; Syamhari Syamhari (Didaktika: Jurnal Kependidikan, 2019)
This research is a classroom action research (Classroom Action Research) which aims to improve students' Indonesian learning outcomes through learning with a process skills approach. The subjects of this study were students of class X-3 SMA Negeri 4 Palopo with 40 students, 12 male students, and 28 female students. Data collection was carried out using learning outcomes tests and observation techniques, and journals. The author made the research instrument in collaboration with a class X Indonesian language teacher at SMA Negeri 4 Palopo. The collected data were analyzed using quantitative and qualitative analysis. The results achieved after applying the process skills approach in learning are: (1) In the first Cycle, the average score of student mastery is 14.71, (2) In the second Cycle, the average score of student mastery was 65.24; (3) There was an increase in student mastery from Cycle I to cycle II of 50.53; (4) The process skills approach can make students more active and enjoy learning Indonesian. From the results of the research above, it can be concluded that the process skills approach can improve the learning outcomes of Indonesian students in class X-3 SMA Negeri 4 Palopo.